Pengaruh Pelaksanaan Jaring Aspirasi Masyarakat dalam Pembentukan Peraturan Daerah Partisipatif - Fatkhurrohman Fatkhurrohman; Miftachus Sjuhad (Jurnal Media Hukum, 2018)
Jaring Asmara were carried out after Regional Regulation drafting was completed by both the executive and the legislative. This research carried out an empirical legal research approach.The results of the research in Malang, Pasuruan and Tulungagung showed that Jaring Asmara activities produced the first few records, all inputs (proposals) from stakeholders were not always fulfilled, especially those that were against the wishes (legal politics) by the legislators. Both things are definitely fulfilled by the legislator when it comes to new policies, information on new legislation, information on new technical procedures. From these findings, it shows that Jaring Asmara is actually a tool to provide opportunities for the community in guarding the formation of a regional regulation to be a little functional (not optimal). Likewise the existence of the thought theory of Philip Nonet and Philip Selznick which is the motor of forming responsive legislation has no effect at all. Jaring Asmara is nothing more than a ceremonial activity where the target is only to drop procedures. It is hoped that in the first year this study will find out the influence of implementing the Jaring Asmara in the formation of participatory local regulations to resolve the problem.